Phosphorylation and O-GlcNAcylation of the PHF-1 Epitope of Tau Protein Induce Local Conformational Changes of the C-Terminus and Modulate Tau Self-Assembly Into Fibrillar Aggregates - Cantrelle, François-Xavier; Loyens, Anne; Trivelli, Xavier; Reimann, Oliver; Despres, Clément; Gandhi, Neha S.; Hackenberger, Christian P. R.; Landrieu, Isabelle; Smet-Nocca, Caroline (Frontiers in Molecular Neuroscience, 2021)
Phosphorylation of the neuronal microtubule-associated Tau protein plays a critical role in the aggregation process leading to the formation of insoluble intraneuronal fibrils within Alzheimer’s disease (AD) brains. In recent years, other post-translational modifications (PTMs) have been highlighted in the regulation of Tau (dys)functions. Among these PTMs, the O-β-linked N-acetylglucosaminylation (O-GlcNAcylation) modulates Tau phosphorylation and aggregation. We here focus on the role of the PHF-1 phospho-epitope of Tau C-terminal domain that is hyperphosphorylated in AD (at pS396/pS404) and encompasses S400 as the major O-GlcNAc site of Tau while two additional O-GlcNAc sites were found in the extreme C-terminus at S412 and S413. Using high resolution NMR spectroscopy, we showed that the O-GlcNAc glycosylation reduces phosphorylation of PHF-1 epitope by GSK3β alone or after priming by CDK2/cyclin A. Furthermore, investigations of the impact of PTMs on local conformation performed in small peptides highlight the role of S404 phosphorylation in inducing helical propensity in the region downstream pS404 that is exacerbated by other phosphorylations of PHF-1 epitope at S396 and S400, or O-GlcNAcylation of S400. Finally, the role of phosphorylation and O-GlcNAcylation of PHF-1 epitope was probed in in-vitro fibrillization assays in which O-GlcNAcylation slows down the rate of fibrillar assembly while GSK3β phosphorylation stimulates aggregation counteracting the effect of glycosylation.